Assessing the Effects of Culture on Managerial Attitudes: A Three-Culture Test - Kelley, Lane; Whatley, Arthur; Worthley, Reginald (Journal of International Business Studies, 1987)
Cross-cultural studies are inherently difficult because the typical research design fails to differentiate cultural from other environmental influences. The present study uses a research design that attempts to isolate the influence of culture. Japanese, Chinese and Mexican managers, their ethnic-American counterparts, and Anglo-Americans are used to test the model. Results indicate unique persistent cultural characteristics with the cultural effect varying among the three groups of managers.